Breastfeeding Duration and Academic Achievement at 10 Years - Oddy, W.; Li, Jianghong; Whitehouse, A.; Zubrick, Stephen; Malacova, Eva (American Academy of Pediatrics, 2011)
rticlesBreastfeeding Duration and Academic Achievement at 10 YearsWendy H. Oddy, PhDa, Jianghong Li, PhDb, Andrew J. O. Whitehouse, PhDa, Stephen R. Zubrick, PhDb, Eva Malacova, PhDa,caTelethon Institute for Child Health Research, Centre for Child Health Research, University of Western Australia, Perth, Australia; andb Curtin Health Renovation Research Institute, Centre for Developmental Health, andcNational Drug Research Institute, Curtin University of Technology, Perth, AustraliaIntroduction The aim of this study was to examine the relationship between duration of breastfeeding and educational outcomes. We hypothesized that longer periods of breastfeeding would predict better educational outcomes in middle childhood.Methods The Western Australian Pregnancy Cohort (Raine) Study used a cohort of 2900 women who were enrolled at 18 weeks' gestation; with 2868 live-born children were followed prospectively. At ~10 years of age, data from 1038 children were linked to standardized mathematics, reading, writing, and spelling scores. Associations between breastfeeding duration and educational outcomes were estimated by using linear models with adjustment for gender, family income, maternal factors, and early stimulation at home through reading.Results Ten-year-old children who were predominantly breastfed for 6 months or longer in infancy had higher academic scores than children who were breastfed for less than 6 months. The effect of breastfeeding on educational outcomes differed according to gender; boys were particularly responsive (in mathematics, spelling, reading, and writing) to a longer duration of breastfeeding.Conclusions Predominant breastfeeding for 6 months or longer was positively associated with academic achievement in children at 10 years of age. However, the effectiveness of breastfeeding differed according to gender; the benefits were only evident for boys.Key Words: breastfeeding • education • child development • Raine StudyAbbreviations: WALNA = Western Australian Literacy and Numeracy Assessment • WAMSE = Western Australian Monitoring Standards in Education • CI = confidence intervalAccepted Sep 10, 2010.